Method Development and Validation ofLevosalbutamol in Pure and Tablet Dosage Formby RP-HPLC - Narendra Nyola, Govinda Samy Jeyabalan, Garima Yadav, Rajesh Yadav ,Subash Gupta, Habibullah Khalilullah (Journal of Applied Pharmaceutical Science)
A simple, rapid and accurate RP-HPLC method was developed for the determination of levosalbutamol in pure and tablet dosage form by RP-HPLC method using C18 BDS column (Phenomenex, 250 x 4.6 mm, 5 μm) in isocratic mode. The mobile phase consisted of Acetonitrile and buffer in the ratio of 20:80 (v/v) was used and maintain the pH 3. The flow rate was maintained at 1 mL/min and the injection volume was 20 μL . Detection wavelength with UV detector at 276 nm and run time was kept 10 min. The retention time of levosalbutamol was 5.4 min. The method was linear over the concentration range 7-12 ug/ml. The recovery was found to be 100.44 ± 0.27%. The validation of method was carried out utilizing ICH-guidelines. The described HPLC method was successfully employed for the analysis of pharmaceutical formulations.
Keywords: HPLC method,Levosalbutamol,Method development.